Análise de Ecoeficiência da Agropecuária nos municípios do bioma Caatinga no Semiárido Nordestino - Araújo, Tanara Jéssica Marques (2022)
Eco-efficiency is an issue that involves the economy and the environment, and its main objective reflects the maximization of economic returns and the minimization of environmental impacts, aiming at a balance between economic and environmental sustainability. In this sense, the present work sought to estimate the agricultural eco-efficiency in the municipalities belonging to the Caatinga biome in the northeastern semi-arid region, using the Data Envelopment Analysis (DEA) method in addition to Multiple Linear Regression and Logit Regression in order to explain the impact of the variables on the index obtained. This research used data from the last Agricultural Census (2017). Data were also extracted from the Greenhouse Gas Emissions and Removals Estimate System (SEEG) in addition to a compilation of data obtained through FIRMS - NASA to determine the number of fires that occurred in this region for the year 2017. The research counted with a total of 1093 municipalities inserted in the Caatinga biome belonging to the northeastern semi-arid region. The results made it possible to categorize the municipalities into eco-efficiency bands, of which 38% of the municipalities belonging to this analysis fit into a very high eco-efficiency level, presenting their results with indices between 0.80 to 1. While the average eco-efficiency index found for the municipalities of the Caatinga biome of the northeastern semi-arid region in 2017 it was 0.718. The benchmark municipalities, that is, the municipalities that are on the ecoefficiency frontier, represent 21.8% of the population, corresponding to 238 municipalities; which configures a scenario in which the municipalities of the Caatinga biome operate, for the most part, below a necessary eco-efficiency that can balance the ecosystem and agricultural production.